Knowledge management, innovation, and entrepreneurship in a changing world - Jennex, Murray E., 1956- (Advances in business strategy and competitive advantage., 2020)
"This book analyzes global aspects of knowledge management from differing cultural perspectives and their use of knowledge and knowledge management. It focuses on the technical issues associated with the creation and implementation of knowledge systems utilizing artificial intelligence, entrepreneurial, and innovative initiatives"--